2023
DOI: 10.1038/s41467-023-40718-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic resolution of substituted amido[2.2]paracyclophanes via asymmetric electrophilic amination

Shaoze Yu,
Hanyang Bao,
Dekun Zhang
et al.

Abstract: Planar chiral [2.2]paracyclophane derivatives are a type of structurally intriguing and practically useful chiral molecules, which have found a range of important applications in the field of asymmetric catalysis and material science. However, access to enantioenriched [2.2]paracyclophanes represents a longstanding challenge in organic synthesis due to their unique structures, which are still highly dependent on the chiral chromatography separation technique and classical chemical resolution strategy to date. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…By measuring the enantioselectivity of recovered starting material 1c (47% ee) and the overall conversion based on 1c (35%), a selectivity ( s ) factor for the reaction was estimated to be 20. Optical rotation comparison showed that the recovered [2.2]paracyclophane 1c was enriched in the ( R p ) enantiomer . Hence, product 3ca is drawn as the product derived from the ( S f ) enantiomer of 1c .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By measuring the enantioselectivity of recovered starting material 1c (47% ee) and the overall conversion based on 1c (35%), a selectivity ( s ) factor for the reaction was estimated to be 20. Optical rotation comparison showed that the recovered [2.2]paracyclophane 1c was enriched in the ( R p ) enantiomer . Hence, product 3ca is drawn as the product derived from the ( S f ) enantiomer of 1c .…”
Section: Resultsmentioning
confidence: 99%
“…Even so, the asymmetric synthesis of functionalized paracyclophanes remains a significant challenge. Typically, enantiomerically pure [2.2]­paracyclophanes are produced either by resolution of diastereomeric derivatives , or by kinetic resolution. In recent years, new approaches using desymmetrization or dynamic kinetic resolution have been developed (Scheme B). These include desymmetrization of meso -diformyl­[2.2]­paracyclophanes by oxidation or reduction and of diamido[2.2]­paracyclophanes by asymmetric electrophilic substitution …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past two decades, transition-metal-catalyzed C–H functionalization has witnessed a booming development, and been successfully employed to access [2.2]­paracyclophane derivatives . Meanwhile, palladium-catalyzed intramolecular C–H activation offers an efficient pathway to afford [2.2]­paracyclophane-fused heterocycles by introducing appropriate coupling partners tethered to the [2.2]­paracyclophane backbone (Scheme b). , Nevertheless, the lower catalytic efficiency due to the constraint by the sterically hindered configuration of the [2.2]­paracyclophane skeleton and the limited types of the tethering coupling partners restrict their further applications. Therefore, the development of intermolecular C–H activation with highly reactive coupling reagents to access [2.2]­paracyclophane-fused heterocycles is highly desirable.…”
mentioning
confidence: 99%